2003
DOI: 10.1182/asheducation-2003.1.350
|View full text |Cite
|
Sign up to set email alerts
|

New Developments in Allotransplant Immunology

Abstract: After allogeneic stem cell transplantation, the establishment of the donor's immune system in an antigenically distinct recipient confers a therapeutic graft-versus-malignancy effect, but also causes graft-versus-host disease (GVHD) and protracted immune dysfunction. In the last decade, a molecular-level description of alloimmune interactions and the process of immune recovery leading to tolerance has emerged. Here, new developments in understanding alloresponses, genetic factors that modify them, and strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 133 publications
(15 reference statements)
1
40
0
2
Order By: Relevance
“…Studies have suggested that expansion of leukemia-associated antigenspecific T cells in the peripheral blood of patients after allogeneic HSCT contribute to the GVL effect. 32,33 Leukemia-associated antigens include an eclectic mix of proteins seen in hematologic malignancies, 18 including cancer/testis antigens such as MAGE A3, developmental proteins such as WT1, and prosurvival/antiapoptotic proteins such as survivin. Several studies have shown that T cells targeting leukemia-and lymphoma-associated antigens can be generated from donors' and patients' periph-…”
Section: Ex Vivo-expanded T Cellsmentioning
confidence: 99%
“…Studies have suggested that expansion of leukemia-associated antigenspecific T cells in the peripheral blood of patients after allogeneic HSCT contribute to the GVL effect. 32,33 Leukemia-associated antigens include an eclectic mix of proteins seen in hematologic malignancies, 18 including cancer/testis antigens such as MAGE A3, developmental proteins such as WT1, and prosurvival/antiapoptotic proteins such as survivin. Several studies have shown that T cells targeting leukemia-and lymphoma-associated antigens can be generated from donors' and patients' periph-…”
Section: Ex Vivo-expanded T Cellsmentioning
confidence: 99%
“…Donor-derived mature T cells are involved in engraftment, graft-versus-host disease (GVHD) and graft-versus-leukemia (GVL) activity, 1 and thus play a major role in determining clinical outcome. However, separation of the detrimental and beneficial effects conferred by donor-derived T cells remains an elusive clinical goal.…”
Section: Introductionmentioning
confidence: 99%
“…10 It may be associated with acute GvHD (aGvHD) and chronic GvHD (cGvHD) as both have a negative impact on immune reconstitution. 11,12 Moreover, the age of recipients affects both CD4 þ recovery and response to mitogens. [13][14][15][16][17] It has been suggested that reconstitution and maintenance of effective T-cell immunity after HSCT is dependent on education of T-cell precursors in the thymus.…”
Section: Introductionmentioning
confidence: 99%